Runtime Complexity TRS:
The TRS R consists of the following rules:

cond1(true, x, y) → cond2(gr(x, y), x, y)
cond2(true, x, y) → cond3(gr(x, 0), x, y)
cond2(false, x, y) → cond4(gr(y, 0), x, y)
cond3(true, x, y) → cond3(gr(x, 0), p(x), y)
cond3(false, x, y) → cond1(and(gr(x, 0), gr(y, 0)), x, y)
cond4(true, x, y) → cond4(gr(y, 0), x, p(y))
cond4(false, x, y) → cond1(and(gr(x, 0), gr(y, 0)), x, y)
gr(0, x) → false
gr(s(x), 0) → true
gr(s(x), s(y)) → gr(x, y)
and(true, true) → true
and(false, x) → false
and(x, false) → false
p(0) → 0
p(s(x)) → x

Rewrite Strategy: INNERMOST

Renamed function symbols to avoid clashes with predefined symbol.

Runtime Complexity TRS:
The TRS R consists of the following rules:

cond1'(true', x, y) → cond2'(gr'(x, y), x, y)
cond2'(true', x, y) → cond3'(gr'(x, 0'), x, y)
cond2'(false', x, y) → cond4'(gr'(y, 0'), x, y)
cond3'(true', x, y) → cond3'(gr'(x, 0'), p'(x), y)
cond3'(false', x, y) → cond1'(and'(gr'(x, 0'), gr'(y, 0')), x, y)
cond4'(true', x, y) → cond4'(gr'(y, 0'), x, p'(y))
cond4'(false', x, y) → cond1'(and'(gr'(x, 0'), gr'(y, 0')), x, y)
gr'(0', x) → false'
gr'(s'(x), 0') → true'
gr'(s'(x), s'(y)) → gr'(x, y)
and'(true', true') → true'
and'(false', x) → false'
and'(x, false') → false'
p'(0') → 0'
p'(s'(x)) → x

Rewrite Strategy: INNERMOST

Infered types.

Rules:
cond1'(true', x, y) → cond2'(gr'(x, y), x, y)
cond2'(true', x, y) → cond3'(gr'(x, 0'), x, y)
cond2'(false', x, y) → cond4'(gr'(y, 0'), x, y)
cond3'(true', x, y) → cond3'(gr'(x, 0'), p'(x), y)
cond3'(false', x, y) → cond1'(and'(gr'(x, 0'), gr'(y, 0')), x, y)
cond4'(true', x, y) → cond4'(gr'(y, 0'), x, p'(y))
cond4'(false', x, y) → cond1'(and'(gr'(x, 0'), gr'(y, 0')), x, y)
gr'(0', x) → false'
gr'(s'(x), 0') → true'
gr'(s'(x), s'(y)) → gr'(x, y)
and'(true', true') → true'
and'(false', x) → false'
and'(x, false') → false'
p'(0') → 0'
p'(s'(x)) → x

Types:
cond1' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
true' :: true':false'
cond2' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
gr' :: 0':s' → 0':s' → true':false'
cond3' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
0' :: 0':s'
false' :: true':false'
cond4' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
p' :: 0':s' → 0':s'
and' :: true':false' → true':false' → true':false'
s' :: 0':s' → 0':s'
_hole_cond1':cond2':cond3':cond4'1 :: cond1':cond2':cond3':cond4'
_hole_true':false'2 :: true':false'
_hole_0':s'3 :: 0':s'
_gen_0':s'4 :: Nat → 0':s'

Heuristically decided to analyse the following defined symbols:
cond1', cond2', gr', cond3', cond4'

They will be analysed ascendingly in the following order:
cond1' = cond2'
gr' < cond1'
cond1' = cond3'
cond1' = cond4'
gr' < cond2'
cond2' = cond3'
cond2' = cond4'
gr' < cond3'
gr' < cond4'
cond3' = cond4'

Rules:
cond1'(true', x, y) → cond2'(gr'(x, y), x, y)
cond2'(true', x, y) → cond3'(gr'(x, 0'), x, y)
cond2'(false', x, y) → cond4'(gr'(y, 0'), x, y)
cond3'(true', x, y) → cond3'(gr'(x, 0'), p'(x), y)
cond3'(false', x, y) → cond1'(and'(gr'(x, 0'), gr'(y, 0')), x, y)
cond4'(true', x, y) → cond4'(gr'(y, 0'), x, p'(y))
cond4'(false', x, y) → cond1'(and'(gr'(x, 0'), gr'(y, 0')), x, y)
gr'(0', x) → false'
gr'(s'(x), 0') → true'
gr'(s'(x), s'(y)) → gr'(x, y)
and'(true', true') → true'
and'(false', x) → false'
and'(x, false') → false'
p'(0') → 0'
p'(s'(x)) → x

Types:
cond1' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
true' :: true':false'
cond2' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
gr' :: 0':s' → 0':s' → true':false'
cond3' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
0' :: 0':s'
false' :: true':false'
cond4' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
p' :: 0':s' → 0':s'
and' :: true':false' → true':false' → true':false'
s' :: 0':s' → 0':s'
_hole_cond1':cond2':cond3':cond4'1 :: cond1':cond2':cond3':cond4'
_hole_true':false'2 :: true':false'
_hole_0':s'3 :: 0':s'
_gen_0':s'4 :: Nat → 0':s'

Generator Equations:
_gen_0':s'4(0) ⇔ 0'
_gen_0':s'4(+(x, 1)) ⇔ s'(_gen_0':s'4(x))

The following defined symbols remain to be analysed:
gr', cond1', cond2', cond3', cond4'

They will be analysed ascendingly in the following order:
cond1' = cond2'
gr' < cond1'
cond1' = cond3'
cond1' = cond4'
gr' < cond2'
cond2' = cond3'
cond2' = cond4'
gr' < cond3'
gr' < cond4'
cond3' = cond4'

Proved the following rewrite lemma:
gr'(_gen_0':s'4(_n6), _gen_0':s'4(_n6)) → false', rt ∈ Ω(1 + n6)

Induction Base:
gr'(_gen_0':s'4(0), _gen_0':s'4(0)) →RΩ(1)
false'

Induction Step:
gr'(_gen_0':s'4(+(_\$n7, 1)), _gen_0':s'4(+(_\$n7, 1))) →RΩ(1)
gr'(_gen_0':s'4(_\$n7), _gen_0':s'4(_\$n7)) →IH
false'

We have rt ∈ Ω(n) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

Rules:
cond1'(true', x, y) → cond2'(gr'(x, y), x, y)
cond2'(true', x, y) → cond3'(gr'(x, 0'), x, y)
cond2'(false', x, y) → cond4'(gr'(y, 0'), x, y)
cond3'(true', x, y) → cond3'(gr'(x, 0'), p'(x), y)
cond3'(false', x, y) → cond1'(and'(gr'(x, 0'), gr'(y, 0')), x, y)
cond4'(true', x, y) → cond4'(gr'(y, 0'), x, p'(y))
cond4'(false', x, y) → cond1'(and'(gr'(x, 0'), gr'(y, 0')), x, y)
gr'(0', x) → false'
gr'(s'(x), 0') → true'
gr'(s'(x), s'(y)) → gr'(x, y)
and'(true', true') → true'
and'(false', x) → false'
and'(x, false') → false'
p'(0') → 0'
p'(s'(x)) → x

Types:
cond1' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
true' :: true':false'
cond2' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
gr' :: 0':s' → 0':s' → true':false'
cond3' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
0' :: 0':s'
false' :: true':false'
cond4' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
p' :: 0':s' → 0':s'
and' :: true':false' → true':false' → true':false'
s' :: 0':s' → 0':s'
_hole_cond1':cond2':cond3':cond4'1 :: cond1':cond2':cond3':cond4'
_hole_true':false'2 :: true':false'
_hole_0':s'3 :: 0':s'
_gen_0':s'4 :: Nat → 0':s'

Lemmas:
gr'(_gen_0':s'4(_n6), _gen_0':s'4(_n6)) → false', rt ∈ Ω(1 + n6)

Generator Equations:
_gen_0':s'4(0) ⇔ 0'
_gen_0':s'4(+(x, 1)) ⇔ s'(_gen_0':s'4(x))

The following defined symbols remain to be analysed:
cond2', cond1', cond3', cond4'

They will be analysed ascendingly in the following order:
cond1' = cond2'
cond1' = cond3'
cond1' = cond4'
cond2' = cond3'
cond2' = cond4'
cond3' = cond4'

Could not prove a rewrite lemma for the defined symbol cond2'.

Rules:
cond1'(true', x, y) → cond2'(gr'(x, y), x, y)
cond2'(true', x, y) → cond3'(gr'(x, 0'), x, y)
cond2'(false', x, y) → cond4'(gr'(y, 0'), x, y)
cond3'(true', x, y) → cond3'(gr'(x, 0'), p'(x), y)
cond3'(false', x, y) → cond1'(and'(gr'(x, 0'), gr'(y, 0')), x, y)
cond4'(true', x, y) → cond4'(gr'(y, 0'), x, p'(y))
cond4'(false', x, y) → cond1'(and'(gr'(x, 0'), gr'(y, 0')), x, y)
gr'(0', x) → false'
gr'(s'(x), 0') → true'
gr'(s'(x), s'(y)) → gr'(x, y)
and'(true', true') → true'
and'(false', x) → false'
and'(x, false') → false'
p'(0') → 0'
p'(s'(x)) → x

Types:
cond1' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
true' :: true':false'
cond2' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
gr' :: 0':s' → 0':s' → true':false'
cond3' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
0' :: 0':s'
false' :: true':false'
cond4' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
p' :: 0':s' → 0':s'
and' :: true':false' → true':false' → true':false'
s' :: 0':s' → 0':s'
_hole_cond1':cond2':cond3':cond4'1 :: cond1':cond2':cond3':cond4'
_hole_true':false'2 :: true':false'
_hole_0':s'3 :: 0':s'
_gen_0':s'4 :: Nat → 0':s'

Lemmas:
gr'(_gen_0':s'4(_n6), _gen_0':s'4(_n6)) → false', rt ∈ Ω(1 + n6)

Generator Equations:
_gen_0':s'4(0) ⇔ 0'
_gen_0':s'4(+(x, 1)) ⇔ s'(_gen_0':s'4(x))

The following defined symbols remain to be analysed:
cond3', cond1', cond4'

They will be analysed ascendingly in the following order:
cond1' = cond2'
cond1' = cond3'
cond1' = cond4'
cond2' = cond3'
cond2' = cond4'
cond3' = cond4'

Could not prove a rewrite lemma for the defined symbol cond3'.

Rules:
cond1'(true', x, y) → cond2'(gr'(x, y), x, y)
cond2'(true', x, y) → cond3'(gr'(x, 0'), x, y)
cond2'(false', x, y) → cond4'(gr'(y, 0'), x, y)
cond3'(true', x, y) → cond3'(gr'(x, 0'), p'(x), y)
cond3'(false', x, y) → cond1'(and'(gr'(x, 0'), gr'(y, 0')), x, y)
cond4'(true', x, y) → cond4'(gr'(y, 0'), x, p'(y))
cond4'(false', x, y) → cond1'(and'(gr'(x, 0'), gr'(y, 0')), x, y)
gr'(0', x) → false'
gr'(s'(x), 0') → true'
gr'(s'(x), s'(y)) → gr'(x, y)
and'(true', true') → true'
and'(false', x) → false'
and'(x, false') → false'
p'(0') → 0'
p'(s'(x)) → x

Types:
cond1' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
true' :: true':false'
cond2' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
gr' :: 0':s' → 0':s' → true':false'
cond3' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
0' :: 0':s'
false' :: true':false'
cond4' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
p' :: 0':s' → 0':s'
and' :: true':false' → true':false' → true':false'
s' :: 0':s' → 0':s'
_hole_cond1':cond2':cond3':cond4'1 :: cond1':cond2':cond3':cond4'
_hole_true':false'2 :: true':false'
_hole_0':s'3 :: 0':s'
_gen_0':s'4 :: Nat → 0':s'

Lemmas:
gr'(_gen_0':s'4(_n6), _gen_0':s'4(_n6)) → false', rt ∈ Ω(1 + n6)

Generator Equations:
_gen_0':s'4(0) ⇔ 0'
_gen_0':s'4(+(x, 1)) ⇔ s'(_gen_0':s'4(x))

The following defined symbols remain to be analysed:
cond1', cond4'

They will be analysed ascendingly in the following order:
cond1' = cond2'
cond1' = cond3'
cond1' = cond4'
cond2' = cond3'
cond2' = cond4'
cond3' = cond4'

Could not prove a rewrite lemma for the defined symbol cond1'.

Rules:
cond1'(true', x, y) → cond2'(gr'(x, y), x, y)
cond2'(true', x, y) → cond3'(gr'(x, 0'), x, y)
cond2'(false', x, y) → cond4'(gr'(y, 0'), x, y)
cond3'(true', x, y) → cond3'(gr'(x, 0'), p'(x), y)
cond3'(false', x, y) → cond1'(and'(gr'(x, 0'), gr'(y, 0')), x, y)
cond4'(true', x, y) → cond4'(gr'(y, 0'), x, p'(y))
cond4'(false', x, y) → cond1'(and'(gr'(x, 0'), gr'(y, 0')), x, y)
gr'(0', x) → false'
gr'(s'(x), 0') → true'
gr'(s'(x), s'(y)) → gr'(x, y)
and'(true', true') → true'
and'(false', x) → false'
and'(x, false') → false'
p'(0') → 0'
p'(s'(x)) → x

Types:
cond1' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
true' :: true':false'
cond2' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
gr' :: 0':s' → 0':s' → true':false'
cond3' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
0' :: 0':s'
false' :: true':false'
cond4' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
p' :: 0':s' → 0':s'
and' :: true':false' → true':false' → true':false'
s' :: 0':s' → 0':s'
_hole_cond1':cond2':cond3':cond4'1 :: cond1':cond2':cond3':cond4'
_hole_true':false'2 :: true':false'
_hole_0':s'3 :: 0':s'
_gen_0':s'4 :: Nat → 0':s'

Lemmas:
gr'(_gen_0':s'4(_n6), _gen_0':s'4(_n6)) → false', rt ∈ Ω(1 + n6)

Generator Equations:
_gen_0':s'4(0) ⇔ 0'
_gen_0':s'4(+(x, 1)) ⇔ s'(_gen_0':s'4(x))

The following defined symbols remain to be analysed:
cond4'

They will be analysed ascendingly in the following order:
cond1' = cond2'
cond1' = cond3'
cond1' = cond4'
cond2' = cond3'
cond2' = cond4'
cond3' = cond4'

Could not prove a rewrite lemma for the defined symbol cond4'.

Rules:
cond1'(true', x, y) → cond2'(gr'(x, y), x, y)
cond2'(true', x, y) → cond3'(gr'(x, 0'), x, y)
cond2'(false', x, y) → cond4'(gr'(y, 0'), x, y)
cond3'(true', x, y) → cond3'(gr'(x, 0'), p'(x), y)
cond3'(false', x, y) → cond1'(and'(gr'(x, 0'), gr'(y, 0')), x, y)
cond4'(true', x, y) → cond4'(gr'(y, 0'), x, p'(y))
cond4'(false', x, y) → cond1'(and'(gr'(x, 0'), gr'(y, 0')), x, y)
gr'(0', x) → false'
gr'(s'(x), 0') → true'
gr'(s'(x), s'(y)) → gr'(x, y)
and'(true', true') → true'
and'(false', x) → false'
and'(x, false') → false'
p'(0') → 0'
p'(s'(x)) → x

Types:
cond1' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
true' :: true':false'
cond2' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
gr' :: 0':s' → 0':s' → true':false'
cond3' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
0' :: 0':s'
false' :: true':false'
cond4' :: true':false' → 0':s' → 0':s' → cond1':cond2':cond3':cond4'
p' :: 0':s' → 0':s'
and' :: true':false' → true':false' → true':false'
s' :: 0':s' → 0':s'
_hole_cond1':cond2':cond3':cond4'1 :: cond1':cond2':cond3':cond4'
_hole_true':false'2 :: true':false'
_hole_0':s'3 :: 0':s'
_gen_0':s'4 :: Nat → 0':s'

Lemmas:
gr'(_gen_0':s'4(_n6), _gen_0':s'4(_n6)) → false', rt ∈ Ω(1 + n6)

Generator Equations:
_gen_0':s'4(0) ⇔ 0'
_gen_0':s'4(+(x, 1)) ⇔ s'(_gen_0':s'4(x))

No more defined symbols left to analyse.

The lowerbound Ω(n) was proven with the following lemma:
gr'(_gen_0':s'4(_n6), _gen_0':s'4(_n6)) → false', rt ∈ Ω(1 + n6)